Hybrid PID-LQR Controller for Dynamic Response and Stability Enhancement of Synchronous Generator’s AVR System - Eze, Paulinus C.; Nwadike, Stanley U.; Oyiogu, Dennis C.; Iroegbu, Mercy Chinenye (Darul Yasin Al Sys, 2025)
The delay in the transition from transient to steady-state conditions in exciter field dynamics is identified as a key factor contributing to inefficiencies in maintaining a stable terminal output voltage in synchronous generators. This delay often results in significant overshoot in the generator’s output voltage, negatively affecting the performance of connected loads such as electric motors. This study aims to develop and evaluate a control strategy based on Proportional-Integral-Derivative and Linear Quadratic Regulator (PID-LQR) models to mitigate this issue. A hybrid control system was designed to enhance voltage stability within the Automatic Voltage Regulator (AVR) of an exciter-based synchronous generator. Using MATLAB simulations, the proposed PID+I-LQR controller demonstrated a reduction in system overshoot from 60.9547% to 1.1524%, representing a 98.1% improvement in voltage stability. Comparative analysis with other control models confirmed the superior performance of the PID-LQR-based controllers in achieving smooth voltage response and convergence to a stable terminal voltage, with the exception of LQI and PID+PD-LQR controllers. The findings underscore the effectiveness of PID-LQR controllers in improving dynamic response and voltage regulation in synchronous generator systems.